The Influence of Leadership, Motivation, and Work Environment on Employee Performance in North Sulawesi Social Service Agency - Richard Edward Fitzgerald Palit; Ratri Wahyuningtyas (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Human resources play a crucial role in achieving the performance objectives of public sector organizations. In the social service agency of North Sulawesi Province, employee performance achievement remains below that of several other regional government institutions, and multiple strategic programs have repeatedly failed to meet their targets. This situation indicates the need to evaluate internal organizational factors that may affect performance. Therefore, this study aims to analyze the influence of leadership style, work motivation, and work environment on employee performance in the agency. A quantitative explanatory method was applied, involving 90 respondents selected through purposive sampling. Data were collected using a structured questionnaire with a 5-point Likert scale and analyzed through PLS-SEM using SmartPLS, incorporating both measurement and structural model assessments. The results show that work motivation and work environment have a significant positive effect on employee performance. Leadership style has no significant effect. The model explains 54.1% of the variance in employee performance, although model fit requires improvement. These findings highlight that organizational efforts should prioritize strengthening employee motivation and creating a more supportive work environment to enhance performance within the public sector.